Dynamic Characteristics of Metro Tunnel Closely Parallel to a Ground Fissure - Nina Liu; Quanzhong Lu; Xiaoyang Feng; Wen Fan; Jianbing Peng; Weiliang Liu; Xin Kang (Complexity)
Shaking table model test and numerical simulation model were conducted on scaled tunnel model to investigate the mechanism and effect of seismic loadings on metro tunnel which is closely parallel to an active ground fissure. Key technical details of the experimental test were set up; for example, similarity relations, boundary conditions, sensors layout, and modelling methods were presented. Synthetic wave, El Centro wave, and Kobe wave were adopted as the input earthquake waves. Results measured from shaking table model and numerical model were compared and analyzed. It is found that the fissure increased the dynamic response features as accelerations and strains of the tunnel, especially in the part close to the fissure. Average incremental percentage of acceleration amplifying coefficient was 8.33% from the wall close to fissure than the symmetrical one. The short distance to fissure led to serious circumferential dynamic strain, while the distance to fissure influenced the axial dynamic strain less. The numerical analysis results have a good correspondence with those of the shaking table model test. The waves at the top of tunnel have more scattering and emission effect. The fissure increases the dynamic response of the tunnel close to it.